Addition to the Flora of Delhi - Naithani, H. B.; Chandra, Sumer; Pal, Mohinder (Indian Forester, 2006)
The Delhi Ridge is a green patch of land considered the "Breathing lung" or "Green lung" of Delhi. Total area of the Ridge is approximately 7,782 ha, which is about 0.6% of Delhi's total geographical area. The area of the Ridge is divided into four zones viz. North Ridge, Central or New Delhi Ridge, South Central Ridge and Southern Ridge with includes the Asola - Bhatti Wildlife Sanctuary. Regarding the flora of Ridge, Maheshwari published the flora of Delhi and included 531 plant species. From the part of Ridge he included 188 plant species. Almost 40 years have passed and no revisionary work on the floristics of Delhi is available except a few sporadic papers. Under a project "Vegetational Survey and Inventorisation of species in the Ridge Forest Delhi" quantitative and qualitative studies of plant were conducted and total 414 species were reported only from the area of the Ridge. Most remarkably, 37 plant species are now being reported for the first time from Delhi